Potential field interpretation of the Baie Verte Peninsula, Newfoundland, utilizing constraints from Lithoprobe East Seismic line 89-13 - Miller, Hugh; Wiseman, R. (Atlantic Geology, 1994)
An understanding of the geological setting of the Baic Verte Peninsula of Newfoundland is central to many interpretations of the Canadian Appalachians. In this paper we present an interpretation of the magnetic and gravity data for the area utilizing constraints from Lithoprobe Vibroscis line 89-13 which traverses the peninsula. The potential field data were processed using a number of techniques to provide shaded relief and other maps providing information on the depth of the sources. Density and magnetic susceptibility data were used in modelling the gravity and magnetic responses for two profiles, one the Lithoprobe line 89-13, and the other a profile farther north. The reflection seismic section was used to constrain the modelling. The Baie Verte Line is interpreted to be confined to the upper few kilometers of the crust. A prominent feature on the seismic section, and its corresponding step on the gravity and magnetic profiles, is interpreted to be the subsurface westward edge of a wedge of intact ophiolitic crust found on the eastern part of the peninsula. This feature is traced away from the seismic line by utilizing its potential field signature. The modelling and processing suggest that the potential field signatures can all be explained by sources in the upper 10 km of the crust, a conclusion consistent with earlier interpretations which were based on potential field data alone.